Quel rôle pour le corpus dans la modélisation ontoterminologique multilingue : l’exemple de la balance des paiements - Carsenty, Stéphane (Studia Romanica Posnaniensia, 2023)
This paper presents the role a specialised corpus can play in the ontoterminological modelling (Roche 2007b) of the balance of payments (IMF, 2009). It presents the domain of the balance of payments and the characteristics of a corpus of texts produced in English, in French and in German by thirteen central banks and statistics offices, which will be used for terminological work. The analysis leads to a typology of the texts grouped in the corpus. Far from only providing examples for knowledge collected from experts, this corpus will be analysed from the very stage of elaborating the concept system.